Laboratory informatics based evaluation of methylene tetrahydrofolate reductase C677T genetic test overutilization - David A Cohen; Brian H Shirts; Brian R Jackson; Lisa S Parker (Elsevier, 2013)
Background: Laboratory data can provide a wide range of information to estimate adherence to guidelines and proper utilization of genetic testing. The methylene tetrahydrofolate reductase (MTHFR) C677T variant has been demonstrated to have negligible utility in patient management. However, the testing of this variant remains pervasive. The purpose of this study was to develop methods to analyze concordance of clinician ordering practices with national guidelines. Methods: We used laboratory data to extract specific data elements including patient demographics, timestamps, physician ordering logs and temporal relationship to chemistry requests to examine 245 consecutive MTHFR tests ordered in 2011 at an academic tertiary center. A comprehensive chart review was used to identify indications for testing. These results were correlated with a retrospective analysis of 4,226 tests drawn at a range of hospitals requesting testing from a national reference laboratory over a 2-year period. MTHFR ordering practices drawn from 17 institutions were examined longitudinally from 2002 to 2011. Results: Indications for testing included cerebrovascular events (40.0%) and venous thrombosis (39.1%). Family history prompted testing in eight cases. Based on acceptable hypercoagulability guidelines recommending MTHFR C677T testing only in the presence of elevated serum homocysteine, 10.6% (22/207) of adult patients met an indicated threshold at an academic tertiary center. Among 77 institutions, 14.5% (613/4226) of MTHFR testing met recommendations. Conclusion: We demonstrate an effective method to examine discreet elements of a molecular diagnostics laboratory information system at a tertiary care institution and to correlate these findings at a national level. Retrospective examination of clinicians' request of MTHFR C677T genetic testing strongly suggests that clinicians have failed to adjust their ordering practices in light of evolving scientific and professional organization recommendations.